2014
DOI: 10.1186/1471-2407-14-914
|View full text |Cite
|
Sign up to set email alerts
|

Number of tumor foci predicts prognosis in papillary thyroid cancer

Abstract: BackgroundPapillary thyroid cancer (PTC) often presents as multifocal. However, the association of multifocality with poor prognosis remains controversial. The aim of this retrospective study was to identify the characteristics of PTC with multiple foci and to evaluate the association between multifocality and prognosis.MethodsWe reviewed the medical records of 496 patients who underwent total thyroidectomy for PTC. Patients were classified as G1 (1 tumor focus), G2 (2 foci), and G3 (3 or more foci). We analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 27 publications
6
53
0
3
Order By: Relevance
“…Results from the Cox proportional hazards regression models identified and verified a series of risk predictors for mortality in DTC, including sex, age, and advanced stage, which were consistent with previous studies 19, 20. Then, we conducted subgroup analysis for the effects of marital status on survival in patients stratified by them.…”
Section: Resultssupporting
confidence: 83%
“…Results from the Cox proportional hazards regression models identified and verified a series of risk predictors for mortality in DTC, including sex, age, and advanced stage, which were consistent with previous studies 19, 20. Then, we conducted subgroup analysis for the effects of marital status on survival in patients stratified by them.…”
Section: Resultssupporting
confidence: 83%
“…The increased proportion of follicular variant PTC in the solitary cases in our study may explain why these aggressive features were less frequent in this group. These findings allude to previous reports correlating multifocality with a more aggressive behavior [7,9,22,25]. Various endeavors to elucidate the origin and behavior of mPTC include both independent clonal origin of these tumors as well as intraglandular spread and subsequent clonal evolution to acquire a more aggressive phenotype [4,11,24,26].…”
Section: Discussionsupporting
confidence: 87%
“…Disease progression and recurrence have been associated with unfavorable pathologic features such as extrathyroidal extension, lymph node and distant metastasis, advanced pathologic stage (Stage III/IV), as well as the presence of BRAF V600E mutation [29,30]. There are also reports associating multifocality with a more aggressive behavior [9,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain studies have indicated that multifocal carcinoma in PTC is positively associated with the incidence of CLNM [14,15], while other studies have argued that there is no association between multifocality and CLNM [16]. In addition, multifocality has found to significantly increase the incidence of recurrence [17].…”
mentioning
confidence: 97%